Problem-Based Learning dan Flipped Classroom: Dapatkah Meningkatkan Prestasi Siswa? - Mardiyah, Lutfiyati; Sunarsi, Anis (Edumatica : Jurnal Pendidikan Matematika, 2024)
The low learning achievement of students is still a problem in the world of education. The application of learning models by less innovative teachers is the main problem. This study aims to examine: (1) the difference in the effect of the combined learning model of Problem-Based Learning with Flipped Classroom and the Problem-Based Learning learning model on student achievement; (2) differences in the effect of academic ability on student achievement; and (3) the effect of the interaction between learning models and academic abilities on student achievement. The sampling technique used a cluster random sampling system. The instrument used was a test which includes a pretest and posttest which functions to determine the level of students' critical thinking skills and academic abilities. This study used an experimental method with a 2x2 factorial design so that four learning groups were formed. The data analysis technique used the Two-Way ANOVA test with unequal cell frequencies. The results of the study show that: (1) there were differences in the effect of the combined learning model of Problem-Based Learning with Flipped Classroom and Problem-Based Learning learning models on student achievement; (2) there were differences in the effect of academic ability on student achievement; and (3) there was no interaction effect between learning models and academic abilities on student achievement. This research is expected to be able to overcome the problem of low student achievement through the application of innovative learning models that can develop students' academic abilities.